The Role of the Surau in Strengthening Islamic Education and Social Cohesion - Erwin Mahrus; Munawir Hasan; Muhammad Syarif Toyyib; Fitri Andriyani (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to examine the role of surau as a center of Islamic education and a medium for strengthening social solidarity in the context of diversity, a social reality in Indonesian society. Using a qualitative case study design, data were collected through participant observation, in-depth interviews, and analysis of relevant documents. The results of this study indicate that the surau functions not only as a space for worship and religious learning, such as Quran recitation, congregational prayer, and the commemoration of Islamic religious holidays, but also as a social arena that facilitates interaction across age groups and ethnic backgrounds. Using Talcott Parsons' AGIL structural-functional framework, this study shows that the surau fulfills adaptive, goal-achieving, integrative, and latency-maintaining functions, collectively helping maintain social cohesion in the community. However, this study identified several obstacles, including limited youth and women's involvement and suboptimal use of digital technology in educational activities. In conclusion, surau remains a strategic institution for community-based Islamic education and social integration. This study contributes theoretically by extending the application of structural-functional analysis to local Islamic educational institutions and, practically, by offering insights into the development of an adaptive, inclusive, and responsive model of religious learning for contemporary Indonesian society.